2021
DOI: 10.1155/2021/1028909
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Tuina Improves Cognitive Impairment in Cerebral Palsy Rats through Inhibiting Pyroptosis Induced by NLRP3 and Caspase-1

Abstract: Cerebral palsy (CP) is a severe cerebral disease with high mortality and morbidity, which leads to great challenges for the suffering children and their families. Hence, the need for the efficacious and safe treatments is urgent. As a physical therapy arising from traditional Chinese medicine (TCM), Tuina has shown multiple effects on various diseases, including cerebral palsy. Nevertheless, the detailed mechanisms of Tuina on CP remain unknown, which impedes its further clinical application. Herein, we explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…TCM treatments, which include massage, acupuncture, herbs, and Qigong, have been practiced in the treatment of CP for a long time. One study showed that TCM may improve the posture balance and cognition of rats with CP ( Niu et al, 2021 ). Increased secretion of dopamine, brain-derived neurotrophic factor, and nerve growth factor were discovered after stimulations on the meridian in rats, which helped repair neuronal damage ( Chuang et al, 2007 ; Tao et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…TCM treatments, which include massage, acupuncture, herbs, and Qigong, have been practiced in the treatment of CP for a long time. One study showed that TCM may improve the posture balance and cognition of rats with CP ( Niu et al, 2021 ). Increased secretion of dopamine, brain-derived neurotrophic factor, and nerve growth factor were discovered after stimulations on the meridian in rats, which helped repair neuronal damage ( Chuang et al, 2007 ; Tao et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is characterized by cell swelling and rupture, cell membrane lysis, cytoplasmic content release into the extracellular compartment, and chromosomal DNA breakage [12,13]. The most commonly activated pathway of heat-induced death is mediated by the NOD-like receptor protein 3 (NLRP3) in ammasome, which consists of NLRP3, apoptosis-associated spot-like protein containing CARD (ASC), and pro-caspase 1 [14,15]. In this activation pathway, NLRP3 is activated in response to intra-and extracellular stimuli, which results in the recruitment of ASC, the binding of ASC to pro-caspase 1, and the assembly of the NLRP3 in ammasome [16].…”
Section: Introductionmentioning
confidence: 99%